N95 respirator and surgical mask effectiveness against respiratory viral illnesses in the healthcare setting: A systematic review and meta‐analysis. Issue 5 (28th October 2021) - Collins, Andrew P.; Service, Benjamin C.; Gupta, Sunny; Mubarak, Naser; Zeini, Ibrahim Mamdouh; Osbahr, Daryl C.; Romeo, Anthony A.
Abstract: Objective: To examine the results, level of evidence, and methodologic quality of original studies regarding surgical mask effectiveness in minimizing viral respiratory illness transmission, and, in particular, the performance of the N95 respirator versus surgical mask. Methods: Meta‐analysis was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines with use of PubMed, MEDLINE, and the Cochrane Library databases. Results: Eight studies (9164 participants) were included after screening 153 articles. Analyses showed statistically significant differences between N95 respirator versus surgical mask use to prevent influenza‐like‐illness (risk ratio [RR] = 0.81, 95% confidence interval [CI] = 0.68–0.94, P  < 0.05), non‐influenza respiratory viral infection (RR = 0.62, 95% CI = 0.52–0.74, P  < 0.05), respiratory viral infection (RR = 0.73, 95% CI = 0.65–0.82, P  < 0.05), severe acute respiratory syndrome coronavirus (SARS‐CoV) 1 and 2 virus infection (RR = 0.17, 95% CI = 0.06–0.49, P  < 0.05), and laboratory‐confirmed respiratory viral infection (RR = 0.75, 95% CI = 0.66–0.84, P  < 0.05). Analyses did not indicate statistically significant results against laboratory‐confirmed influenza (RR = 0.87, CI = 0.74–1.03, P  > 0.05). Conclusions: N95 respirator use was associated with fewer viral infectious episodes for healthcare workers compared with surgical masks. The N95 respirator was most effective in reducing the risk of a viral infection in the hospital setting from the SARS‐CoV 1 and 2 viruses compared to the other viruses included in this investigation. Methodologic quality, risk of biases, and small number of original studies indicate the necessity for further research to be performed, especially in front‐line healthcare delivery settings.